MRC2 Promotes Proliferation and Inhibits Apoptosis of Diabetic Nephropathy - Lanlan Li; Xin Chen; Henglu Zhang; Min Wang; Weiping Lu (Analytical Cellular Pathology)
Diabetic nephropathy (DN) is an important microvascular complication of diabetes and is the main cause of end-stage renal disease. Type 2 mannose receptor C (MRC2) is a member of the mannose receptor protein family, which has been confirmed to have the ability to promote the cell migration signaling pathway and invasion. By complementary DNA chip screening and analysis, we found that the expression of MRC2 was upregulated in the kidneys of mice with diabetic nephropathy. However, the role of MRC2 in diabetic nephropathy is still unclear. This work studied the effect of MRC2 on diabetic nephropathy. After verifying the results of the chip by quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting, we used small interfering RNAs (siRNAs) to knock down the expression of MRC2 in mouse mesangial cells (MMCs) and analyzed the level of cell proliferation and apoptosis using western blotting, Cell Counting Kit-8, and flow cytometry. The results showed that the MRC2 knockdown inhibited MMC proliferation and induced cell apoptosis. These results suggest that MRC2 may be a molecular marker and a therapeutic target for diabetic nephropathy.